Islamic Religious Education Learning Media In The Empowered Kurikulum To Form Akhlakul Karimah At Smpn 3 Sumberjaya - Komariah Komariah (Journal of Multidisciplinary Sustainability Asean, 2024)
Background. In the era of the independent learning curriculum, the use of appropriate learning media is very important in supporting an effective learning process, especially for Islamic Religious Education (PAI) and Budi Pekerti subjects. This research was conducted at State Junior High School 3 Sumberjaya, which previously faced problems such as student indiscipline, cheating, lack of respect for teachers, and low student interest in joining school organizations. Purpose. This research aims to identify appropriate learning media for PAI and Budi Pekerti in the independent learning curriculum, analyze the obstacles in its implementation, and find solutions to overcome these obstacles. Method. The research used is observation, interview, documentation and qualitative research type with descriptive approach. The results of data analysis in this study use the data collection stage, reduction stage, presentation stage, verification stage and conclusion drawing. Results. The results revealed that audiovisual, visual, and audio learning media are effective types of media in learning PAI and Budi Pekerti in the independent learning curriculum. The obstacles faced include the lack of teacher insight in using learning media, limited economic resources, and lack of student cooperation. Proposed solutions include teacher training on making practical, economical, and creative learning media, and collaboration with parents. Conclusion. The appropriate learning media in the independent curriculum for learning PAI and Budi Pekerti are audiovisual, visual, and audio media. To overcome this, teachers need to attend training and collaborate with parents in developing and using learning media effectively.